2018
DOI: 10.1016/j.actbio.2018.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Transparent titanium dioxide nanotubes: Processing, characterization, and application in establishing cellular response mechanisms

Abstract: Titanium dioxide (TiO) nanotubes are known to strongly enhance bone/mesenchymal stem cell behavior and, consequently, have gained attention as potential osteogenic surface treatments for titanium-bone implants. The exact mechanism by which TiO nanotubes influence cellular function remains controversial, partly due to limitations in existing cellular imaging methods with opaque substrates. This work identifies fabrication conditions for the successful production of transparent TiO nanotube arrays with tailorabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
5
1
1
Order By: Relevance
“…In the past, there was a canine model experiment which observed the morphology of connective tissue around the porcine type I collagen-coated titanium surface, but the outcome of this previous study demonstrated a similar appearance when compared to the finding around the turned titanium surface. 40 The reason why the outcome of the present research differed from that of the forementioned study possibly lies in the fact that the type I collagen covering the pCol-group implant was not just coated but had an EPF-induced perpendicular orientation, 17,22,23 which seemed to potentially play a role in priming the collagen fibers in a more perpendicularly arranged manner.…”
Section: Quantitative Evaluation Of the Laminin-5 And Collagen Fibers...contrasting
confidence: 64%
See 1 more Smart Citation
“…In the past, there was a canine model experiment which observed the morphology of connective tissue around the porcine type I collagen-coated titanium surface, but the outcome of this previous study demonstrated a similar appearance when compared to the finding around the turned titanium surface. 40 The reason why the outcome of the present research differed from that of the forementioned study possibly lies in the fact that the type I collagen covering the pCol-group implant was not just coated but had an EPF-induced perpendicular orientation, 17,22,23 which seemed to potentially play a role in priming the collagen fibers in a more perpendicularly arranged manner.…”
Section: Quantitative Evaluation Of the Laminin-5 And Collagen Fibers...contrasting
confidence: 64%
“…The surface was created through an electrochemical anodization process using a titanium piece (anode) and a copper piece (cathode). 17,22,23 This way, the negatively charged C-terminus of collagen fibers could be attached perpendicularly to the positively charged TNT surface. These collagen fibers, aligned in an ideal manner, not only demonstrated strong binding resistance against sonification forces, but also inhibited formation of epithelial sheets, suggesting the potential for preventing epithelial downgrowth between the collagen fibers and the titanium surface.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the outstanding mechanical property, chemical stability and biocompatibility, titanium (Ti) alloy implants have been widely used for orthopedic and dentistry surgeries to restore damaged tissue and structure during the past decades. 1 However, many undesirable complications occurred after surgery, especially poor osteointegration and bacterial infection. 2 To further avoid adverse events and optimize the performance of implants, nano-surface modification may be a promising strategy and become one of the recent research hotspots.…”
Section: Introductionmentioning
confidence: 99%
“…It should be underlined that tubular structures grow directly out of the Ti substrate and no further immobilization process is required for application, e.g., in electrochemical water splitting. Moreover, the method can be applied to titanium of different shapes, from flat plates and wire [ 25 ] to screws and semitransparent substrates (e.g., indium tin oxide) coated with a layer of Ti [ 26 ]. The ability to form an ordered nanostructure over large areas [ 27 ] is also beneficial for further commercialization.…”
Section: Introductionmentioning
confidence: 99%